XR SKETCH ASSISTANTS FOR EARLY CHILDHOOD ON ART EDUCATION ENHANCING 4C - Iriaji, Iriaji; Rakhmat Taufani, Agusta; Ratnawati, Ike; Aruna, Alby; Marcelliantika, Adinda; Putri Surya, Eka; Atma Wijaya, Ginanjar (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2024)
This research focuses on the evaluation and integration of Extended Reality (XR) Sketch Assistants technology in arts education for early childhood, specifically reviewing its effect on the development of 4C skills (Critical Thinking, Communication, Collaboration, and Creativity). Through quantitative and qualitative experimental designs with the ADDIE Model instructional stages, this study implements an observation, interview and content analysis method approach to collect comprehensive data regarding the application and impact of XR technology in the context of arts education. Preliminary results show that XR Sketch Assistants substantially improve critical thinking, communication, collaboration, and creativity skills in young children. The implementation of this technology in arts teaching and learning provides an interactive platform that encourages visual exploration of sketches, creative problem solving, and innovative artistic expression. The children involved in the study demonstrated enhanced abilities to interpret, analyze, and create works of art with deeper understanding and greater creativity.